Pendidikan Sebagai Pembentuk Karakter Era Modern Menurut Perspektif Ibnu Khaldun - Muhammad Rizki; Putri Dewi Sinta; Herlini Puspika Sari (Reflection : Islamic Education Journal, 2025)
The role of education in shaping character has been a subject of discourse throughout history, with its significance amplified in the face of contemporary challenges. This study examines the relevance of Ibn Khaldun's educational philosophy in the context of modern character formation. The reseaarch aims to analyze Ibn Khaldun's perspective on education and its potential application in contemporary character-building efforts. A qualitative approach is employed, focusing on a comprehensive review of secondary sources and scholarly interpretations of Ibn Khaldun's educational theories. The study synthesizes various perspectives on Ibn Khaldun's educational philosophy and examines their applicability to current educational practices and challenges. This approach allows for a broader understanding of Ibn Khaldun's ideas within the context of modern educational needs. The study reveals that Ibn Khaldun's educational theory emphasizes the integration of religious, moral, and practical knowledge in character development. His holistic approach to education, which includes the cultivation of critical thinking, social skills, and ethical values, aligns closely with current educational needs. The findings suggest that Ibn Khaldun's educational principles can significantly contribute to addressing modern character-building challenges, particularly in fostering resilience, cultural understanding, and ethical decision-making among students. This research provides valuable insights for educators and policymakers in developing comprehensive character education programs that balance traditional wisdom with contemporary demands. Moreover, it highlights the importance of revisiting historical educational philosophies to inform and enrich modern a pedagogical practices, especially in the realm of character education.